Aksesibilitas Pendidikan Agama Islam Terhadap Siswa Penyandang Disabilitas di SMP Muhammadiyah 9 Yogyakarta - Muh Husain Kamaruddin; Ismaya Ismaya; M Yunus Sudirman (EduPsyCouns: Journal of Education, Psychology and Counseling, 2023)
This research is motivated that students with disabilities have the same rights as other students in getting Islamic religious education. Based on school realities, teaching inclusion classes requires specific skills. This study aims to describe and critically analyze data on the implementation of inclusion-based Islamic religious education for students with disabilities at SMP Muhammadiyah 9 Yogyakarta, whether Islamic religious learning is easy and accessible or not. This type of research is qualitative research, taking the case of SMP Muhammadiyah 9 Yogyakarta. Data collection is carried out by conducting observations, documentation, and interviews. Data analysis is done by giving meaning to the data that has been collected, and from that meaning conclusions are drawn. The results of this study state that: 1). Inclusive-based PAI learning cannot be separated from the learning components, namely curriculum, educators, students, materials, methods, media and evaluation. The curriculum used is a curriculum prepared by the PP Primary and Secondary Education Council. Muhammadiyah refers to the 2006 National curriculum for grades 8 and 9, as well as the 2013 curriculum for grade 7. Learning methods and media are tailored to the needs of students with disabilities with duplication, and modification (accommodative curriculum model). Islamic Religious Education materials can already be accessed by students with disabilities even though they have not been maximized. 2). The obstacles of PAI teachers in learning Islam for people with disabilities are the lack of understanding and skills of teachers in teaching, PAI teachers have only attended inclusive school training once, there has been no intensive coordination between PAI teachers and special assistance teachers, PAI teachers have not mastered the use of sign language and the use of learning media that has not been maximized for students with disabilities